IDENTIFIKASI KEKUATAN DAN KELEMAHAN POTENSI KECAMATAN SIKAKAP KABUPATEN KEPULAUAN MENTAWAI UNTUK DIKEMBANGKAN SEBAGAI DESTINASI WISATA - Yudhytia Wimeina; Rafidola Mareta Riesa (Politeknik Negeri Padang, 2018)
Most of tourism research findings indicated tourism activities shares positivities such as welfareness of the communities suround the tourism area. In contradiction, Sikakap as a district within Mentawai Islands regency, is not benefited by the tourist visit whose come for surfing, a special interest tourism. Therefore, trough this research, Sikakap potency is being analysis for the possibility to be developed as tourism destination. In finding the potency of Sikakap, the SWOT approach was utilised to analysed the 4A (accesibilities, attractions, ammenities, ancillary services) components of destination. The result shows eventhough there were more weaknesess than strength, Sikakap still able to be developed as a tourism destination.